الترجمه الاليه من العربيه الى الانكليزيه لبعض انواع الجمل الفعلية بحث مستل من اطروحة دكتوراة - عبد الباقي, سلمى (University of Thi-Qar Journal of Science, 2012)
The field of natural language processing is interested in how to find representive and  remedial computational ways and devices for natural languages which facilitate the dealing with the computer by using the natural language and the cancelling of the linquistics barrier rising between the computer and its users . This interest is motivated by the fast development of computer systems and the internet . Besides language represents the basic nuclens for the unity of science and intellect and the common ground of humanitarian sciences. Arabic is one of the most complex languages as it has characteristics that set it apart off  other languages . These characteristics have been a rich resource of study for researchers in the field of Arabic , computational linquistics . This research is considered one of the source as it is expected to play a significant role in the study of Arabic , computationallinquistics . Text translation especially instant translation is regarded one of the demands of the  present time imposed by the technology of information exchange through the internet and its necessity in the media and conferences. The research focuses on the design of model for a machine translation from Arabic to English which translates some Arabic verbal sentences of different orders . The proposed model consists of three main parts which one analysis , dictionary , and generation . The analysis part performs all the processes related to the clauses entered and their analysis in away that guarantees obtaining their vocabulary items.